The Influence of the Use of Image Media on Student Learning Outcomes in Science Subjects Material about the Energy Sources of Students in Grade VI SDN No 107467 Gunung Para - Kinda Meilani; Minar Trisnawati Tobing; Sukardo Sitohang (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study was to determine the presence or absence of the effect of the use of image media on student learning outcomes in science subjects material about the energy sources of students in grade VI SDN No. 107467 Gunung Para. The population in this study were all children in class VI SD Negeri 107467 Gunung Para. The sample used in this study was a grade VI student at SD Negeri No. 107467 Gunung Para. The total number of class VI students is 22 students who consist of 10 male students and 12 female students. The design used in this Kuanti is pre-test and post-test. This design involves class (one-group pretest-posttest design), namely the experimental class and the control class. The data obtained were analyzed using non -parametric statistics Wilcoxon signs rank test. Based on the results of the test and analysis of the data that has been carried out, the calculation results with T-test obtained t hitung of 11,287 which is then compared with t tabel of 1.721 with df = 21 and a significant level of 0.05. The difference is said to be significant if t hitung > t tabel. If t hitung > t tabel then Ho is rejected and Ha is accepted, and if t hitung < t tabel then Ho is accepted and Ha is rejected. Based on the data it turns out t hitung > t tabel (11,287> 1,721) means that there is an influence of the use of image media on student learning outcomes in science subject matter about the energy source of class VI SD Negeri 107467 Gunung Para.